Correction of vertebral deformations in children and adolescents with spinal hernias - I. A. Shavyrin; S. V. Kolesov (Лечащий Врач, 2021)
Optimum therapeutic measures aimed at improving the outcomes of patients with neuromuscular spinal deformations against meningocele were developed. Materials and Methods: 8 patients aged 3 to 17 years with neuromuscular spinal deformations against meningocele, surgical treatment was performed one stage — and two-five patients — three patients, two patients underwent resection of the vertebral column (VCR). As a result of correction of scoliosis treatment an average of 62%, the value of thoracic / thoracolumbar kyphosis after surgery could bring to the physiological (40 degrees).